Latent Inhibition as a Biological Basis of Creative Capacity in Individuals Aged Nine to 12 - Lorca Garrido, Antonio José; López-Martínez, Olivia; de Vicente-Yagüe Jara, María Isabel (Frontiers in Psychology, 2021)
This study focuses on latent inhibition, a mechanism behind selective attention, as the biological basis of creativity in schoolchildren. The main objective of this study is to know if low levels of attention positively affect the levels of creativity manifested in individuals between the ages of nine and 12. The design of this study is non-experimental with an explanatory-correlational cross-sectional quantitative approach. In order to achieve the objective suggested, several education centres located in Murcia were selected, in which 476 students took part in a creativity test (PIC-N), a attention test (D2) and another test about intelligence depending on the educational level (BADYG/E2r or BADYG/E3r). The results obtained were that selective attention was negatively correlated with graphic creativity, understanding that behind it lies the latent inhibition and that when certain levels of intelligence are present, this negative correlation increases. In this way, it is demonstrated the existence of creative and inattentive subjects at the same time.